Dialect Geography of Javanese in Wonogiri Regency - Hadi, Nikolaus Rendi Prasetya; Utomo, Y. Sandi Wahyu (Jurnal CULTURE (Culture, Language, and Literature Review), 2025)
This research investigates the Javanese dialect used in Wonogiri Regency and compares it with standardized Javanese. The analysis focuses on dialect characteristics, vocabulary distribution, and phonological and morphological features. The data were collected from native Javanese speakers in eight districts: Manyaran, Selogiri, Wonogiri, Ngadirojo, Sidoharjo, Jatisrono, Slogohimo, and Purwantoro. Data collection was carried out using questionnaires and interviews. The data were analyzed through a distributional method using contrasting techniques and further interpreted using a qualitative descriptive approach. The findings revealed several lexical and phonological variations from standard Javanese, such as noto, ndhodo, nendhang, ngajul, luwe, wuto, iso, enjoh, karo, ambek, and lan. Based on dialectometric calculations, the Javanese spoken in Wonogiri is not classified as a distinct dialect but rather as a speech variation (28.81%).